2021
DOI: 10.1186/s13002-021-00435-2
|View full text |Cite
|
Sign up to set email alerts
|

An ethnopharmacological survey and comparative analysis of plants from the Sudhnoti District, Azad Jammu and Kashmir, Pakistan

Abstract: Background This is the first comprehensive report on the traditional and novel uses of medicinal plants practiced by the indigenous communities of the Sudhnoti district of Azad Jammu and Kashmir (AJK), Pakistan. The area is rich in folklore and indigenous medicinal knowledge due to a unique tribal composition and socioeconomic conditions. This study aimed to document traditional knowledge of native plant use by the local communities, particularly those used for therapeutic purposes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
4
9
0
Order By: Relevance
“…For instance, Z . armatum is planted as the second most important medicinal species in Pakistan [ 32 ]. The fruit pulp of Zanthoxylum could be extended to treat skin diseases, toothache, fever, and stomach ache [ 24 , 26 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Z . armatum is planted as the second most important medicinal species in Pakistan [ 32 ]. The fruit pulp of Zanthoxylum could be extended to treat skin diseases, toothache, fever, and stomach ache [ 24 , 26 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…D. ambrosioides is cited in the literature for sputum, cough, bruises, flu, tuberculosis, urinary diseases, scarring and pain in the body (Cock et al 2021;Farias et al 2019, Magalhães et al 2019. M. arvensis is seen in the treatment of abdominal pain (diarrhea), gastric and intestinal problems, stomach acidity, earache and respiratory problems, menstrual pain and anxiety (Khan et al 2021;Magalhães et al 2019;Rehman et al 2017). L. alba is used in the treatment of digestive and respiratory diseases, hypertension, headache, skin diseases, injuries, insomnia, colic, heart and liver diseases, lack of appetite, diarrhea, tonic, dizziness, worms (Hennebelle et al 2008;Magalhães et al 2019;Medeiros et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…al. 2006;Ahmed et al, 2015;Khan et al 2021). An important point noted during the current study that the aged informants (65 %) have more traditional knowledge than the females (35 %) and young ones.…”
Section: Demographic Features Of Informantsmentioning
confidence: 99%
“…Local communities depend on ethnoveterinary herbal therapies for treatments of livestock ailments. However, few ethnobotanical studies of medicinal plants have been reported in District Sudhanoti for the treatments of human ailments (Ishtiaq et al 2016;Khan et al 2021). The area of District Sudhanoti is rich of ethnobotanical knowledge due to diverse tribal communities and socioeconomic condition (Khan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation